Seleksi Aksesi Padi Lokal Bangka Melalui Pengujian Variabilitas dan Heritabilitas - Prayoga, Gigih Ibnu; Mustikarini, Eries Dyah; Pradika, Desti (Universitas Bangka Belitung, 2017)
Selection of parent plant is the first step in hybridization activities. The parent plant usually come from germplasms because it has a high diversity and good potential. Testing the potential of germplasm can be done by variability and heritability test. The purpose of this research was to selection of parent plant for plant breeding activity based on the value of variability and heritability. The research was conducted at the Experimental Garden of Faculty of Agriculture, Fisheries, and Biology, Bangka Belitung University. The research used experimental methods by was Randomized Block Design (RBD) with 3 blocks. The treatment are 7 accessions is Grintil, Balok Runti, Mukud Besak, Mayang Curui, Payang Tebing, Balok Lutong and Balok Lukan Jintan. The results showed that there were character differences between 7 local rice accessions of Bangka. The 7 local rice accessions of Bangka have high heritabilities value on The results showed that there were character differences between 7 local rice accessions of Bangka. The 7 local rice accessions of Bangka have high heritabilities values for plant height, flowering time, long panicle, total empty grain, harvest time, long seed, seed width, weight of 1000 seeds, total seeds, and weight seed/plant. Wide variability was found in long seed character. Balok Runti and Payak Tebing were recommended as the parent plants for further breeding activities.